The experience of being at the university from the perspective of an indigenous postgraduate student - Gilza Ferreira de Souza Felipe Pereira; Wagner Roberto do Amaral; Jenifer Araujo Barroso Bilar (Arizona State University, 2020)
The present work, the result of the dialogical authorship between an indigenous academic and researcher and two non-indigenous researchers involved in this theme, intends to contribute to greater visibility and recognition of the trajectories of indigenous scholars and professionals formed by public universities in a recent context of affirmative actions that enable the entry and permanence of indigenous and afro-descendant populations in Brazil and Latin America. These subjects have been inserted in the higher education and intensively worked in the most different spaces of student stay, of political struggles, of social and cultural recognition, not only in academic environments but also in the daily life of their communities of belonging. It is a qualitative research, carried out through bibliographical review, documentary research and the report of the experience of an indigenous academic and researcher. The undertaken reflections highlight the daily challenges experienced by indigenous peoples as researchers, intellectuals, protagonists, subjects and authors of the knowledge produced by them, inaugurating an unprecedented moment in the history of indigenous people in Brazil and contributing to new strategies of resistance and strengthening of indigenous people struggles.